Pengaruh Price, People Dan Physical Evidence Terhadap Kepuasan Konsumen Pada Swalayan Pasaraya Di Desa Watugede Kecamatan Puncu - Rahayu, Lia Putri Dwi; Laksono, Sonny Subroto Maheri; Hastuti, Sriwahyuni Mega (Otonomi, 2024)
This research is motivated by the increasing level of competition in the retail world. To attract and retain customers to continue shopping, retail companies continue to try to find new strategies that are different from other competitors. This research aims to determine the influence of Price, People and Physical Evidence simultaneously and partially on consumer satisfaction at Supermarkets in the Watugede Village Area, Puncu District. This research is quantitative in nature, primary resources from questionnaires distributed to Ds supermarket consumers. Watugede District. Puncu. The sample used was 97 respondents. The test tools used in this research were the classical assumption test, normality test, multicollinearity test, and heteroscedasticity test, with the help of SPS version 25. There is a partial influence between price (X1) on consumer satisfaction at Pasaraya Supermarkets, where the results of the t test obtained a significant value of 0.020 <0.05, which means Ho is rejected and Ha1 is accepted. There is a partial influence between people (X2) on consumer satisfaction at Pasaraya Supermarkets, where the t test results obtained a significant value of 0.000 < 0.05, which means Ho is rejected and Ha2is accepted. There is a partial influence between physical evidence (X3) on consumer satisfaction at Pasaraya Supermarkets, where the t test results obtained a significant value of 0.006 < 0.05, which means Ho is rejected and Ha3 is accepted. There is a simultaneous influence between price(X1), people (X2), and physical evidence (X3) on consumer satisfaction at Pasaraya Supermarkets, where the f test results obtained a significant value of 0.000 < 0.05, which means Ho is rejected and Ha4 is accepted.